Oxidative stress products and managements in atopic dermatitis - Luo, Yingqiang; Hu, Jun; Zhou, Zihao; Zhang, Yan; Wu, Yaguang; Sun, Jiaying (Frontiers in Medicine, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder that affects a significant portion of the global population, severely impacting the quality of life and causing physical and psychological distress of patients. Oxidative stress, resulting from an imbalance between oxidation and antioxidation activities, plays a pivotal role in the pathogenesis of AD. Monitoring oxidative stress products can offer valuable insights into the development of AD and highlight essential clinical and therapeutic effects. Additionally, evidence suggests that antioxidant strategies can alleviate or avert oxidative damage induced by free radicals and offer significant promise in the treatment of AD. In addition to directly utilizing natural products and nanomaterials for antioxidant interventions, these can also be incorporated into hydrogels, which help repair the skin barrier and support the sustained release of therapeutic agents. Furthermore, microneedles provide a minimally invasive method for delivering antioxidants to the deeper layers of the skin, enhancing treatment efficacy. This review aims to summarize the role of the oxidative stress in the pathogenesis of AD, focusing in the main oxidative products (DNA, protein, and lipid oxidation products), as well as antioxidant therapeutic approaches involving natural products, nanomaterials, hydrogels, and microneedles. Understanding these biomarkers and antioxidant therapy approaches provides important insights into the management of AD.